Pemberdayaan Masyarakat Desa Melalui Kegiatan Pengembangan Soft Skill Digitalisasi UMKM dalam Meningkatkan Keterampilan Wirausaha Masyarakat Desa Kaliangkrik - Wandha Nur Handayani; Much. Fadli Putra Syaeli; Salsabilla Brita Maharani; Sri Wahyuni (Jurnal Bina Desa, 2026)
Kaliangkrik Village is one of the villages located in Kaliangkrik District, Magelang Regency. The life of its people is still thick with culture and religious beliefs. However, this does not limit the enthusiasm and creativity of its people in developing business ideas and improving their quality of life. One of the economic activities that continues to be developed by its people is MSMEs. There are quite a lot of MSMEs business actors in Kaliangkrik Village, but they are still limited in their marketing activities. MSMEs actors still market through word of mouth, consigning products to shops and opening their own shops. A group of students held a seminar to help improve the knowledge and skills of its people. The seminar was related to community empowerment related to "Development of Soft Skills for Digitalization of MSMEs ". This seminar activity aims to equip MSMEs actors to move up a class to become a business supported by  technological advances, both for management and marketing.